Empowering Women’s MSMEs through Islamic Financial Literacy and Accountable Financial Management: A Case Study of POKSILA Mekar Indah, Semarang City - Santosa, R Ery Wibowo Agung; Sukamto; Ridwan, Mohammad; Kristiana, Ida; Saputro, Bagastyo Adji (Society : Jurnal Pengabdian Masyarakat, 2026)
The Elderly Group (POKSILA) Mekar Indah in Muktiharjo Kidul Village, Semarang City, has productive economic potential through processing patchwork waste into household utensils. However, this partner group faces serious challenges in the form of limited capital and the trap of high-risk illegal loans. This community service aims to provide sharia financial assistance through the Qardhul Hasan scheme to strengthen partners' capital and financial literacy. The implementation method is carried out in three stages over one year: (1) socialization and training on sharia financial management, (2) implementation of Qardhul Hasan funds through partnerships with third parties (BPRS Artha Surya Barokah), and (3) coaching, production assistance, and evaluation using the 5P of Credit principle. The results of the service show that this program has succeeded in shifting the burden of high-interest debt to soft sharia loans, improving the financial health of individual members, as well as increasing the organization's cash accumulation through product diversification such as laundry bags and doormats. The trust of local stakeholders has also increased, which is marked by the strengthening of partner product marketing networks. Overall, the Qardhul Hasan-based joint responsibility pattern has proven to be effective as a safe financial solution for the elderly in running their productive businesses.